Rising Powers in Complex Regimes: South African Norm Shopping in the Governance of Cross-Border Investment. Issue 5 (28th July 2020) - Murray-Evans, Peg
ABSTRACT: This article offers a critical engagement with the literature on contemporary global power shifts and the phenomenon of 'regime complexity'. It does so by focusing on South Africa's role in the governance of cross-border investment, and using this case to explore the strategies used by rising powers to pursue their strategic aims in institutionally complex and fragmented global governance regimes. This article situates an understanding of regime complexity within a critical constructivist literature that highlights the ambiguity of international norms and the relationship between power and strategic rhetorical action. It argues that complex regimes create space for agency and strategic action by states and highlights one specific strategy – norm shopping – that rising powers can use to legitimate their actions and challenge dominant norms in complex regimes.